Integrating Problem-Based Learning and the Teaching at the Right Level Approach to Improve Students’ Collaboration Skills - Alfi Andriani; Eli Trisnowati (Yayasan Nurul Yakin Bunga Tanjung, 2025)
This study aimed to enhance Grade VIII students’ collaboration skills by integrating the Teaching at the Right Level (TaRL) methodology with the Problem-Based Learning (PBL) model. Conducted as classroom action research (CAR) involving 32 students from Class VIII F at SMP Negeri 1 Magelang, the study was implemented over two cycles, each comprising the stages of planning, implementation, observation, and reflection. Data were collected through observation sheets, questionnaires, and interviews, and analyzed using descriptive quantitative techniques. The findings revealed consistent improvement across five indicators of collaboration skills, with increases of 15%, 19%, 17%, 22%, and 18% after two cycles. The overall average score rose from 61% in the pre-cycle to 72% in Cycle I and 91% in Cycle II. These results indicate that the integration of PBL and TaRL effectively fostered students’ teamwork competencies. The study contributes to the growing body of evidence on how learner-centered and level-based instructional approaches can synergistically promote active engagement, peer collaboration, and the development of 21st-century skills in middle school education.